RED CELL AND PLASMA RADIOACTIVE COPPER IN NORMAL AND ANEMIC DOGS - Yoshikawa, H. (The Rockefeller University Press, 1942)
Following ingestion of radioactive copper by the dog, the metal appears quickly in the plasma, the concentration reaching its peak in from 2 to 5 hours, after which it falls abruptly. Demonstrable amounts are still present after 2 days. The radioactive copper likewise appears rapidly in the circulating red blood cells, and there is a slow but gradual increase in its concentration over a 2 day period. It is suggested by the data that in the animals in which hematopoietic activity is accelerated the uptake of radio-copper is somewhat more extensive. The possibility that this is due to greater adsorption by the new red cells in these instances is not ruled out.